Resisting cooperation against crime: Britain's extradition controversy, 2003-2015 - Efrat, Asif (International journal of law, crime and justice)
International extradition serves as a crucial tool for fighting crime. In the era of globalization, the growth of transnational crime has led governments to facilitate extradition and relax some of the protections and safeguards that this process traditionally includes. Does this trend toward easier extradition enjoy public support? The recent debate over Britain's extradition arrangements provides insight into this question. This debate demonstrates a sharp divide between the law-enforcement community, on the one hand, and, on the other hand, the public, politicians, and NGOs. Representative of the judiciary, prosecution, and police supported the removal of barriers to extradition, whereas politicians and NGOs - highlighting flaws in the justice systems of the United States and EU countries - demanded greater protections. The British experience enriches our understanding of international extradition and offers a unique window into the domestic political controversy surrounding it. It shows that public support for extradition is less robust than we might expect - a cause for concern in the present era of rising nationalism.